Odpowiedzi

Najlepsza Odpowiedź!
2010-03-22T17:16:41+01:00
A)7×+3=9+2×
7x - 2x = 9 - 3
5x = 6/:5
x = 1 i 1/5

b)9-8×=15-6×
-8x+6x = 15 - 9
-2x = 6/:2
-1x = 3
x = -3

c)6(3+2×)=2(×-4)
18+12x = 2x - 8
12x - 2x = -18 - 8
10x = -26/:10
x = - 2 i 3/5

d)4(¼-5×)-⅓(9-6×)=1
1 - 20x - 3 - 2x = 1
-22x = 3
-3 = 22x/:22
-3/22 = x

Pozdrawiam =)
2010-03-22T17:21:35+01:00
A)7x+3=9+2x
7x-2x=9-3
5x=6
x=6/5
x=1.2

b)9-8x=15-6x
-8x+6x=15-9
-2x=6
x=6/-2
x=-3

c)6(3+2x)=2(x-4)
18+12x=2x-8
12x-2x=-8-18
10x=-26
x=-26/10
x=-2.6

d)4(1/4-5x)-1/3(9-6x)=1
1-20x-3-2x=1
-20x-2x=1+3-1
-22x=3
x=3/-22
x=-3/22